2019
DOI: 10.1111/bjep.12309
|View full text |Cite
|
Sign up to set email alerts
|

Boredom begets boredom: An experience sampling study on the impact of teacher boredom on student boredom and motivation

Abstract: BackgroundBoredom is a common complaint among students. Boredom was previously found to be negatively associated with academic outcomes, such as academic motivation, strategies, and achievement. It is of interest to understand students’ in‐class boredom, especially factors that might exacerbate it.AimsThe current study examines the influence of teacher's boredom on students’ in‐class boredom and learning experience. It aims to understand the relationship between teacher boredom, students’ perceived teacher bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Furthermore, enthusiasm has been demonstrated as an important teacher quality [13], and a well-slept teacher has been shown preferable for students' academic motivation and in-class satisfaction [14]. Conversely, teachers being perceived as bored may reduce students' learning motivation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, enthusiasm has been demonstrated as an important teacher quality [13], and a well-slept teacher has been shown preferable for students' academic motivation and in-class satisfaction [14]. Conversely, teachers being perceived as bored may reduce students' learning motivation [15].…”
Section: Discussionmentioning
confidence: 99%
“…This boredom is not strongly linked to the general social studies subject matter but could be because the teacher's presentation was not stimulating and had limited novelty. Tam et al (2020) provide evidence of this boredom dynamic. In their study, for two weeks, high school teachers self-reported their boredom during instruction.…”
mentioning
confidence: 85%
“…Research has highlighted numerous detrimental effects of boredom on students’ academic lives in many different grades such as primary school [ 17 ], secondary school and universities [ 18 ]. Notably, numerous studies emphasize that boredom is related to higher attentional problems [ 5 ], lower lecture attendance [ 19 ], lower effort regulation [ 5 ], lower intrinsic and extrinsic motivation to learn, which in turn erodes academic achievement [ 16 , 20 , 21 ]. Moreover, as highlighted by Daschmann et al [ 22 ], boredom is positively correlated with lower grades, enhanced absenteeism, and a higher risk of dropping out.…”
Section: Introductionmentioning
confidence: 99%
“…In the university context, a study [ 32 ] showed that the expectation for success and subjective task value encourage choice, effort, persistence and continuation in engineering for undergraduate engineering students. In the same way, Neuville et al, [ 21 ] showed that the intention to persist in the first year of university was influenced by students’ perception of their probability of success and by the value and the interest they had for their studies. Neuville et al, [ 21 ] further revealed that students who had a negative emotional adjustment (i.e., a negative emotional state like feelings of distress or a negative physical state like a somatic problem) showed a lower intention to persist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation